(untitled) (Bangladesh Journal of Animal Science, 2023)
The present study was undertaken to investigate the efficacy of three diluters (Triladyl, Andromed and Tris) for the production of frozen semen in Black Bengal goat and their effect on conception rate. Over the course of 6 months, data from six bucks were collected. Each collected sample was diluted with Triladyl, Andromed and Tris diluter, filled into 0.50 ml straws, sealed and equilibrated at 5℃ for freezing. The motility, viability and morphology were evaluated after dilution and in every step of cryopreservation (after equilibration, after freezing and after thawing). It became clear that motility and sperm viability of the frozen thawed semen differed significantly (p<0.05) but differed insignificantly (p>0.05) immediate after dilution among the diluters. The motility of frozen thawed semen was 42.50%±1.71, 34.67%±1.67 and 28.71%±1.55 in Triladyl, Andromed and Tris diluter, respectively. The viability of frozen thawed semen was 40.51%±1.78, 32.24%±1.52 and 26.84%±1.56 in Triladyl, Andromed and Tris diluter, respectively. In case of morphology, it differed insignificantly (p>0.05) among the diluters in every step of cryopreservation. Higher percentage of normal spermatozoa was found in Triladyl based diluter (87.11%) in frozen thawed semen. After 15 days of sample preparation, the motility of prepared sample was again checked to ensure the quality of frozen semen in liquid nitrogen (LN). It differed insignificantly (p>0.05) with frozen thawed semen after 24 hours of production. The obtained conception rate was 38% for Triladyl, 35% for Andromed and 27% for Tris diluter. The results of the study revealed that cryopreservation of buck semen revealed good results with Triladyl diluter followed by Andromed and Tris diluter. Bangladesh Journal of Animal Science 52 (4): 105-113